Epigenetic reprogramming by histone acetyltransferase HAG1/AtGCN5 is required for pluripotency acquisition in Arabidopsis - Kim, Ji-Yun; Forner, Joachim; Lohmann, Jan U. (The EMBO journal, 2018)
Abstract Shoot regeneration can be achieved in vitro through a two-step process involving the acquisition of pluripotency on callus-induction media (CIM) and the formation of shoots on shoot-induction media. Although the induction of root-meristem genes in callus has been noted recently, the mechanisms underlying their induction and their roles in de novo shoot regeneration remain unanswered. Here, we show that the histone acetyltransferase HAG1/AtGCN5 is essential for de novo shoot regeneration. In developing callus, it catalyzes histone acetylation at several root-meristem gene loci including WOX5, WOX14, SCR, PLT1, and PLT2, providing an epigenetic platform for their transcriptional activation. In turn, we demonstrate that the transcription factors encoded by these loci act as key potency factors conferring regeneration potential to callus and establishing competence for de novo shoot regeneration. Thus, our study uncovers key epigenetic and potency factors regulating plant-cell pluripotency. These factors might be useful in reprogramming lineage-specified plant cells to pluripotency.
Gesehen am 18.10.2019